2001
DOI: 10.1164/ajrccm.164.3.2011041
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alterations of Gene Complexes by Cystic Fibrosis Sputum

Abstract: Gene complexes with optimal physicochemical characteristics for cystic fibrosis (CF) gene therapy in vitro may become inactive in vivo as a result of destruction upon interaction with CF mucus. Therefore, we examined in this study to what extent main sputum components (linear DNA, mucin, phosphatidylcholine, phosphatidylglycerol, and albumin) may disintegrate lipoplexes. We found that mixing linear DNA with lipoplexes, in concentration ratios as occurs in the mucus of patients with CF in clinical studies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 27 publications
3
70
0
Order By: Relevance
“…In a previous study we experimentally showed that lipoplexes mixed with CF sputa indeed started to dissociate when the linear DNA:pDNA concentration ratio in the mixtures was above 1.6. 8 From the dissociation experiments on the GL67 lipoplexes by CF mucus components we showed that only albumin was able to disassemble these lipoplexes (although artificially) at concentration ratios that exist in vivo (Tables 2 and 3). Indeed, dissociation was observed from an albumin:pDNA concentration ratio of 40 onwards.…”
Section: Does the Behavior Of Lipoplexes In The Presence Of Individuamentioning
confidence: 94%
See 4 more Smart Citations
“…In a previous study we experimentally showed that lipoplexes mixed with CF sputa indeed started to dissociate when the linear DNA:pDNA concentration ratio in the mixtures was above 1.6. 8 From the dissociation experiments on the GL67 lipoplexes by CF mucus components we showed that only albumin was able to disassemble these lipoplexes (although artificially) at concentration ratios that exist in vivo (Tables 2 and 3). Indeed, dissociation was observed from an albumin:pDNA concentration ratio of 40 onwards.…”
Section: Does the Behavior Of Lipoplexes In The Presence Of Individuamentioning
confidence: 94%
“…Indeed, we recently showed that CF mucus components clearly interact physicochemically with cationic lipoplexes. 8 However, besides this report, there is no additional information pertaining to this matter. In particular, it has not been determined how structural changes to the gene complexes by CF mucus constituents influence their transfection activity.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations